THE PRACTICE OF PEDAGOGICAL DIGITAL COMPETENCE AMONG ESL LECTURERS - Sidra Naim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
With the goal of having students graduate with 21 century skills, there is a gap on who are the ambassador of the integration of digital skills. This is where language lecturers can be seen as role models of digital skills. Yet, there is a deficiency in studies looking at ESL lecturers’ use of technology in terms of pedagogical use. Taking in the lens of Krumsvik’s Teachers’ Digital Competence Model, the purpose of the qualitative study is to explore the practice of Pedagogical Digital Competence (PDC) among English as Second Language (ESL) lecturers through 14 in-depth interviews analyzed by Nvivo 12 software to define the themes and codes that emerged. The results revealed the lecturers’ use of ICT in the mastery of digital tools utilized for support their teaching, technological challenges faced during the implementation of said skills, as well as the cognizance of ethics in navigating the online world. It is interesting to note that the ESL lecturers highlighted policies restricting usage of technology in terms of formal assessments. The findings are highly relevant to bridging the gap in the growing literature of Malaysian ESL Lecturer’s PDC.